Experimental and numerical study on sooting transition process in iso-octane counterflow diffusion flames: Diagnostics and combustion chemistry. (October 2021) - Zhao, Xuan; Xu, Lei; Chen, Chen; Chen, Mingfei; Ying, Yaoyao; Liu, Dong
Abstract: The present work focused on the combustion chemistry in sooting transition process in iso -octane counterflow diffusion flames. A series of iso -octane flames ranging from sooting-free to heavy-sooting were investigated by stepwise increasing the oxygen concentration ( X O ) in the oxidizer stream. In particular an optical approach with two different algorithms based on the three wavelengths distribution of flame images captured by digital single lens reflex (DSLR) camera was proposed to identify the critical condition for the sooting transition process. The results showed that the sharp increase in signal ratio of red luminosity with simultaneously obvious decrease in signal rations of blue luminosity could be used as an effective indicator of sooting onset in flames. On-line gas chromatography (GC) measurements were used to investigate the flame chemistry and determine quantitative mole fraction profiles of stable and reactive species formed in the combustion process. Particular attention was given to the combustion chemistry changes caused by the occurrence of sooting transition. Numerical kinetic simulations were performed along with the comparisons with experimental results to obtain deep insights into the sooting transition process, with focus on benzene chemistry considering the critical role of benzene formation in the subsequent large aromatic species/soot formation process. In most cases, the trend observed in the experiments could be satisfactorily reproduced and explained by the models. For major species and C1–C4 species, it can be seen that the concentration increased with the increase of X O in sooting transition process. For the decomposition of fuel and the formation of benzene, the influence in sooting transition process was mainly reflected in the contributions of different pathways due to temperature effects. The impact of sooting transition on flame chemical structure was mainly reflected in the growth of PAHs. The increasing trend for the PAHs growth caused by the increase of oxygen concentration in the transition process was more and more obvious. Highlights: Critical sooting transition condition was identified with a novel optical method. Combustion chemistry in the sooting transition process was studied. Kinetic analysis was performed to get insights into sooting transition process. The growth of PAHs was promoted during the sooting transition process.